Sikap Peduli Sosial Siswa Sekolah Dasar di Kabupaten Kuningan (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
The purpose of this study is to find out the social care attitudes of elementary school students in Kuningan Regency. This study uses a quantitative approach with a survey method. The subjects in this study are grade IV students of public elementary schools in Kuningan Regency with a sample of 10 elementary schools with 178 respondents.  Data were collected using questionnaires that included five characteristics of social caring attitudes: sharing, cooperation, honesty, helping, and donating. The results of the study show that in general, students show a relatively low level of social concern, with an average percentage of 49.983%. Of the five indicators observed, only two aspects were included in the medium category, namely sharing (50.98%) and honesty (51.96%). These two indicators show that some students still have the ability to show empathy and openness in social interactions, although they are not optimal. Meanwhile, three other indicators are in the low category, namely cooperation (49.37%), helping (49.435%), and donors (48.175%).